Knowledge management and the political–pedagogical project in Brazilian schools - Costa, Andréia de Cássia Gonçalves (2021)
Knowledge Management as a strategy to improve the quality of the institutional environment can be related to the coordination of activities that create, store and share knowledge. School Management has to deal with different tasks, such as planning, organization, leadership, guidance, monitoring and evaluation of all the processes necessary to ensure the promotion of students’ learning and training. In this context, the Political–Pedagogical Project assists School Management, since it is an important document for the school organization, containing the school’s identity as well as the plan to achieve the best teaching and learning process for the school community. In this sense, the objective of this research was to demonstrate how the Political–Pedagogical Project can promote Knowledge Management at the school level. The methodology used was exploratory and bibliographic research. The results obtained in this paper show that the Political–Pedagogical Project strengthens School Management when it is supported by Knowledge Management, considering that there is an improvement in the promotion of the quality of the organizational environment, as well as the elucidation of effective learning for teachers and students through democratic management.